Implementation of System Development Life Cycle (SDLC) on IoT-Based Lending Locker Application - Melinda Melinda; Shaquille Rizki Ramadhan Na; Yudha Nurdin; Yunidar Yunidar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Libraries are social institutions that provide information services that can be accessed publicly to meet the information needs of librarians. Based on the results of a survey conducted on 58 students who have visited the library of the Electrical and Computer Engineering Department of the Universitas Syiah Kuala, an information system was needed that provided research book information related to the author's name, year of writing, field concentration, and abstract of the research book, and there was a division of categories based on field concentration, and there was an online borrowing feature. Based on these problems, this study aims to implement an Android application system with IoT-based lending lockers using the SDLC (system development life cycle) prototyping method. This study produces an application with a locker-based online lending feature, several other features as the user desires, and one prototype lending locker. The locker-based online lending system integrated with ESP32-WROOM-32 can connect to Firebase storage and send locker key codes to Firebase so that the application can access them. Through experiments and tests conducted on the application, it is obtained that the application can access the locker key code and display it to the user. The application has also been validated using black-box and white-box testing and can be accepted by users based on the System Usability Scale (SUS) average score with a very feasible interpretation category.